Novel 2‐formylpyridine 4‐allyl‐S‐methylisothiosemicarbazone and Zn(II), Cu(II), Ni(II) and Co(III) complexes: Synthesis, characterization, crystal structure, antioxidant, antimicrobial and antiproliferative activity. (20th December 2019) - Balan, Greta; Burduniuc, Olga; Usataia, Irina; Graur, Vasilii; Chumakov, Yurii; Petrenko, Peter; Gudumac, Valentin; Gulea, Aurelian; Pahontu, Elena
Abstract : New zinc (II), copper (II), nickel (II) and cobalt (III) complexes, [Zn (HL)2 ]I2 (1), [Cu (HL)Cl2 ] (2), [Cu (HL)Br2 ] (3), [Cu (HL)(H2 O)2 ](ClO4 )2 (4), [Ni (HL)2 ]I2 ·H2 O (5), [Co(L)2 ]Cl (6), [Co(L)2 ]NO3 (7), [Co(L)2 ]I·[Co(L)2 ](I3 ) (8) were obtained with 2‐formylpyridine 4‐allyl‐ S ‐methylisothiosemicarbazone (HL ). The isothiosemicarbazone ligand was characterized by NMR ( 1 H and 13 C), IR spectroscopy and X‐ray diffraction. All the complexes were characterized by elemental analysis, IR, UV–Vis, ESI‐MS spectroscopy, molar conductivity, magnetic susceptibility measurements. X‐ray diffraction analysis on the monocrystal and powder elucidated the structure of the complexes 1, 5, 7 and 8 . T he ligand and the complexes were tested for their antioxidant and antimicrobial activity against Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae and Candida albicans. Also, the antiproliferative properties of these compounds on human leukemia HL‐60, human cervical epithelial HeLa, human epithelial pancreatic adenocarcinoma BxPC‐3, human muscle rhabdomyosarcoma spindle, large multinucleated RD cells and normal MDCK cells have been investigated. The nickel complex 5 and cobalt complexes 6, 7 showed promising antiproliferative activity and low toxicity. Abstract : The nickel complex 5 and cobalt complexes 6, 7 showed promising antiproliferative activity and low toxicity.